Control and Supervision of a Solar Electric System - Benabed, Khadidja; Amine, Boudghene Stambouli; Noureddine, Benabadji (Institute of Advanced Engineering and Science, 2019)
Energy consumption is one of the biggest concerns because it is increasing and it has a great impact on our environment. Photovoltaic energy is a possible response to the challenges of the energy transition of tomorrow. For proper operation, the solar photovoltaic system needs a rigorous supervision of its electrical and physical parameters. Monitoring is one of the foundations of photovoltaic maintenance engineering. This article describes the design and realization of a solar monitor for the monitoring of the correct operation of a mini power plant from panels photovoltaic.